Ageing fundus degenerations of Macaca fascicularis on multi-modal imaging and histopathology: Similarities and differences compared to human. (July 2022) - Zhang, Xiongze; Li, Miaoling; Li, Bihai; Liao, Nanying; Wei, Zhiyuan; Gao, Jiangmei; Sun, Yunxiao; Chen, Jianhuan; Rao, Junhua; Wen, Feng
Abstract: To characterize the ageing fundus degenerations in Macaca fascicularis, we used multimodal imaging including color fundus photograph, spectral domain optical coherence tomography, fundus autofluorescence, fundus fluorescence angiography, and indocyanine green angiography (ICGA) to survey and track fundus changes of 84 Macaca fascicularis, ranging from 5 to 24 years old over 2 years, and followed by hematoxylin-eosin (HE) and immunofluorescence (IF) staining. The Macaca fascicularis in our cohort showed ageing characteristics different from human, including the more common yellow dot maculopathy, the unique appearance of patchy hyperautoflurescence, and the absence of subretinal drusenoid deposit, basal laminar deposit, geographic atrophy or choroidal neovascularization. Same with human, hard drusen, soft drusen, atherosclerosis, tessellated retina, staining of vessels in peripheral choroid on late-phase ICGA, and peripheral hard drusen were detected. HE and IF staining suggested the patchy hyperautoflurescence to be drusenoid deposits. BMI were significantly higher in the Macaca fascicularis with yellow dot maculopathy and hard drusen, compared to the ones without (p < 0.05). Our study reveals fundus degenerations that develop with ageing in the nonhuman primate of Macaca fascicularis . Their differences and similarities compared to human worth notice by future translational research in degenerative fundus diseases, especially age-related macular degeneration. Highlights: Higher frequency of yellow dot maculopathy. Presence of patchy hyperautoflurescent spots. Absence of the extracelluar deposits-subretinal drusenoid deposit or basal laminar deposit. Fundus degenerations appeared earlier but were less advanced, i.e. no geographic atrophy or macular neovascularization.